Vibrationally resolved photoelectron angular distributions of ammonia. Issue 13 (16th March 2022) - González-Collado, Celso M.; Plésiat, Etienne; Decleva, Piero; Palacios, Alicia; Martín, Fernando
Abstract : Photoelectron angular distributions of ammonia reflect, under special circumstances, the double-well potential of its umbrella mode. Abstract : We present a theoretical study of vibrationally resolved photoelectron angular distributions for ammonia in both laboratory and molecular frames, in the photon energy range up to 70 eV, where only valence and inner-valence ionization is possible. We focus on the band resulting from ionization of the 3a1 HOMO orbital leading to NH3 + in the electronic ground state, , for which the dominant vibrational progression corresponds to the activation of the umbrella inversion mode. We show that, at room temperature, the photoelectron angular distributions for randomly oriented molecules or molecules whose principal C 3 symmetry axis is aligned along the light polarization direction are perfectly symmetric with respect to the plane that contains the intermediate D 3h conformation connecting the pyramidal structures associated with the double-well potential of the umbrella inversion mode. These distributions exhibit symmetric, nearly perfect two-lobe shapes in the whole range of investigated photon energies. In contrast, for molecules where the initial vibrational state is localized in one of the two wells, a situation that can experimentally be achieved by introducing an external electric field, the molecular-frame photoelectron angular distributions (MFPADs) are in general asymmetric, but the degree of asymmetry of the two lobes dramatically changes and oscillates with photoelectron energy. We also show that, at ultracold temperatures, where all aligned molecules initially lie in the delocalized ground vibrational state, the photoelectron angular distributions are perfectly symmetric, but the two-lobe shape is only observed when the final vibrational state of the resulting NH3 + cation has even parity. When the latter vibrational state has odd parity, the angular distributions are much more involved and, at photoelectron energies of ∼10 eV, they directly reflect the bi-pyramidal geometry of the molecule in its ground vibrational state. These results suggest that, in order to obtain structural information from MFPADs in ammonia and likely in other molecules containing a similar double-well potential, one could preferably work at ultracold temperatures, which is not the case for most molecules.